GENDER RESEARCH IN PAKISTAN: A SCOPING REVIEW - Asad, Nargis; Allana, Anita Anis (European Scientific Journal, ESJ, 2015)
Researchers focusing on gender issues usually concentrate on how people perceive and interpret gender, understand or construct sex and gender etc. Much needs to be explored and understood in relation to research and concepts of gender studies. The present study â€œGender Research in Pakistan: A Scoping Reviewâ€ was carried out with the purpose of mapping literature on gender research in Pakistan, further exploring how gender concepts like social construction of roles, power relationships, division of labor/resources are understood and constructed by researchers in social science research. Also the review intended to provide grounds for critiquing how researchers problematize and integrate gender concepts in their phenomenon of interest and while doing so what research methods are applied by them. The paper will share the importance of gender sensitive research and the results of the scoping review carried out. It shall also attempt to document methodological gaps in the retrieved literature, concluding with some recommendations for way forward.